Analysis of Public Information Systems on The Quality of Public Services in Asam Kumbang Village, Medan Selayang District - Sitta Mutia Rizkya; Yunita Sari Rioni; Ayu Kurnia Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the application of public information systems in improving the quality of public services in Asam Kumbang Village, Medan Selayang District. The method used is descriptive qualitative through observation, interviews, and documentation of officials and the community. The results of the study show that the use of public information systems, such as computers and social media (WhatsApp, Instagram, TikTok, and Facebook), has helped speed up the service process and increase information transparency. However, its implementation is not yet optimal due to unstable internet connections, limited technological facilities, and the continued use of manual/face-to-face methods. Overall, the public information system contributes positively to the efficiency and openness of services, but infrastructure and human resource capacity need to be improved so that public services become more effective and accountable.